Management of febrile illness in rural Guinea over a seven-year period: A retrospective study - Karifa Kourouma; Fassou Mathias Grovogui; Alexandre Delamou; Mahamoud Sama Chérif; Brecht Ingelbeen; Abdoul Habib Beavogui; Johan van Griensven; Emmanuel Bottieau (Public Library of Science (PLoS), 2022)
Introduction Febrile illnesses constitute a major clinical challenge in tropical settings. We aimed to assess the frequency, presentation and management of febrile illness at two health facilities in Forécariah, Guinea, with a focus on appropriateness of antibiotic prescription. Materials and methods This was a retrospective study conducted in patient files in a health center and a district hospital. Proportions of antibiotic prescription were determined by age group and syndromes as well as appropriateness of antibiotic prescription using the WHO model list (2019). Results From 2014 to 2020, 23,583 of 62,185 (38.0%) visits were related to febrile illness. Most patients with fever were female (56.1%) and evaluated at the health center (81.0%). Gastrointestinal (40.6%) and respiratory syndromes (36.8%), and undifferentiated fever (30.0%) were the most common presentations. Malaria was confirmed in 61.3% of the cohort. Overall, the rate of antibiotic prescription was high (14,834/23,583, 62.9%), mostly among patients aged <5 years (5,285/7,566, 69.9%), those with respiratory (7,577/8,684, 87.3%) and gastrointestinal (6,324/9,585, 66.0%) syndromes. Moreover, 7,432/14,465 (51.4%) patients with malaria were also prescribed an antibiotic. Penicillin (42.0%), cotrimoxazole (26.3%) and quinolones (18.7%) were the most frequently prescribed antibiotics. Overall, appropriateness of antibiotic prescription was low (38.3%), and even more so in patients with respiratory (29.1%) and gastrointestinal (25.8%) syndromes. Conclusions Febrile illness is a major cause of consultation in rural Guinea. Rate of antibiotic prescription was high, even in confirmed malaria and was often considered inappropriate. There is a pressing need to investigate the etiological spectrum and improve the diagnostic approach of febrile illness in Guinea.